(untitled) (KMC Journal, 2025)
With the physical descent and loneliness that come with aging, strong social networks are critical to preserving an older person’s well-being. The study focuses on the impact on the psychological well-being of people. The study took place at Lamki Chuha Municipality, Kailali district in Nepal. In this study, 249 elderly people aged 60 years and above were systematically selected through random sampling, and data were collected through a descriptive survey using a cross-sectional design. Data were generated using face-to-face interviews administered by developing a questionnaire. Descriptive statistics and analysis of variance (ANOVA) were used to analyze how social support affects the emotional well-being of respondents using SPSS (version 20). The findings indicate that more than one-third of the elderly feel that their families do not support them adequately, 42.6 percent indicated rejection as an issue, and 38.2 percent stated communication barriers as a reason for lack of support. This study showed that structural support was very important since it had connections to both financial resources and knowledge, but it was a friendship that was perceived to be most valuable, and it influenced older people to a very great extent. As a result of the findings of this study, specific measures should be implemented frequently for these unique groups.